Protective Humoral Immunity Induced by Lipopolysaccharide Incorporated Liposome in Mice Against Shigella flexneri Infection - Naser, Haider Hussain; Salih, Shahlaa M; Al-Shaibani, Abdulwahid B (Al-Nahrain Journal of Science, 2018)
This study was conducted to determine the role of lipopolysaccahride-liposome conjugate (LPS-LIP) as a potential vaccine against shigellosis in mice by determining the IgG titer. One hundred stool samples were collected from patients with diarrhea from different hospitals in Baghdad city during the period December 2011-May 2012. Thirty isolates were suspected to be Shigella. Four isolates of Shigella flexneri were obtained after performing some biochemical tests and Api System. Antibiotic sensitivity test was carried out and results revealed that all isolates were resist to some antibiotics used in this study. One isolate was selected for LPS extraction by phenol hot water extraction method. Chemical characterization of the extracted LPS revealed that the carbohydrate content was 2.34 mg/ml, while the protein concentration was 0.52µg/ml. Partial purification of the extracted LPS was carried out by using gel- filtration chromatography on Sephacryl S-200 and results showed that three peaks were obtained and protein, carbohydrate concentration were estimated for each peak. The second peak observed to have the highest carbohydrate content was (25%). and the lowest contaminated protein was (0.001%). The partial purified LPS was analyzed by Sodium Dodecyl Sulphate Gel Electrophoresis (SDS-PAGE) and results reveled that two bands with molecular weights 100 and 150 KDa were present. Band with MW 100 kDa represented LPS. IgG titer was estimated by Elisa technique. A significant increase in IgG titer was recorded in mice treated with conjugate after infection with S. flexneri.